IMPLEMENTASI DAN MANFAAT PENERAPAN AKUNTANSI DIGITAL TERHADAP PERTUMBUHAN PERUSAHAAN - burhanuddin, chairul ihsan (AkMen JURNAL ILMIAH, 2024)
Digitalization in every line of the Company's operations is a process that cannot be avoided. One of the operational and supporting processes of the Company that later changed was the presentation of financial statements (accounting processes). Change is one word that must be implemented by the Company in order to make fast, effective, and responsible decisions. So that the presentation of fast and precise financial statements becomes a must in the Company. With fast data processing, it is expected that the owner of the Company has information that is realtime, and informative. So that the entire change process provides added value to the business owned by the Company. The question that arises is what distinguishes manual processes and digital processes, what are the advantages of digital processes, and how to implement these digital processes. This research aims to reveal facts through selective data and information related to the process of digitizing data. In the process, the research method used is qualitative descriptive by selectively collecting related research results in order to produce the latest information directly related to the accounting digitization process. The results revealed that several important factors in the digitization process that need to be considered are the availability of sufficient funds, infrastructure, adequate human power capabilities, and sufficient digitalization implementation strategies. In addition, another problem is how to get around the rejection of digital processes from within the Company.